Enhancing Presentation via Bluetooth™ Technology in Higher Educational Institutes - Shoib, Fadhlina (Universiti Teknologi Petronas, 2004)
This paper is intended to present a project in introducing a new generation of wireless technology, Bluetooth™ to the higher educational institute and its future perspectives in Malaysia. One question arises, how Bluetooth™ technology can benefit educators to deliver their knowledge presentations in the feasible and easiest ways? Consequently, the short-range wireless connectivity technology lets electronics devices automatically recognize, connect and transfer data between each other. This technology is aimed high in eliminating wires and cables between both a handheld device and personal computer (PC) through the Bluetooth™ USB Dongle. Moreover, it is also purposely done to deliver better service for lecturer to control slide presentation. The information for the project is being acquired through the research on the Bluetooth™ specifications and some methods are being carried out from time to time in area of observation, preliminary information gathering, data collection through questionnaires, data analysis and simulation development in the methodology which is required to achieve its goal. The architecture and simulation of the transmission between a Bluetooth™ enabled handheld device and a PC facilitated with a Bluetooth™ USB Dongle will be proposed to represent the project. This study's conclusion denotes that wireless technology is essential in enhancing presentations delivery that can help a better communication between lecturers and students.